Conductive compliant mechanisms: Geometric tuning of 3D printed flexural sensors - Frederik Grønborg; Tiberiu Gabriel Zsurzsan; Anders Egede Daugaard; Jon Spangenberg; David Bue Pedersen (Additive Manufacturing Letters, 2022)
Additive manufacturing of thermoplastic conductive polymer composites offers interesting opportunities for customizing compliant flexural sensors. The study aimed to show that additive manufacturing could be used to fabricate flexural sensors for evaluating the effect of sensor geometry on the sensor output. Prior literature has primarily focused on material optimization rather than geometrical design. The results of this paper show that the signal amplitude between geometrically different flexural sensors with the same footprint can increase ∼28 times. In addition, the bending force is found proportional to the signal amplitude. Thus, concentrating the bending to a small section increases the signal amplitude but also increases the effect of material relaxation broadening the hysteresis loop. This study highlights the importance of considering the geometrical design when fine-tuning additive manufactured flexural sensors. In future work, it is paramount to improve reproducibility, signal linearity, and investigate the effects of geometry on other sensor parameters.